Portable trip distance calculator - Mohd 'Izzat, Mat Hassan (2012)
The purpose of this project is to developed a micrcontroler-based portable trip distance calculator. This device is needed for cyclers in this generation for gathering information and improving their performance by cycling. It can be used for any kind of bicycle which definitely has difference size of wheel or tire. Nowadays, the increasing numbers of urbanite taking cycling as fitness regime or hobby show that youth and also folks concern more about their healthy lifestyle. Moreover, they will also need to improve their stamina in order to sustain and maintain their healthy life by knowing their limits or average fitness. Therefore, this project objective is to develop an algorithm that utilize wheel rotation to determine distance travel and also to develop a circuit for hardware that take signal from a sensor placed to detect rotating wheel, process it and display the calculated distance travelled by the cyclers. The objective is succesfully achive after taking some experimental testing of the product.